The impact of family ownership on firm performance: A study on Vietnam - Nguyen Minh Hai; Bao Ngoc Do; Trung Thanh Ngo (Cogent Economics & Finance, 2022)
The purpose of this study is to examine the effect of family ownership and other factors on firm performance in Vietnam and to determine the optimal level of family ownership required to maximize firm performance. The study employs the quantitative method of panel-corrected standard errors (PCSE) regression to analyze data on 31 nonfinancial enterprises listed on the Ho Chi Minh City Stock Exchange (HOSE) in Vietnam between 2011 and 2019. The firm performance is analyzed from both a market perspective (via Tobin's Q) and an accounting perspective (via return on assets [ROA]). The U-shaped curve illustrating this effect show that the relationship between family ownership and the performance of Vietnamese enterprises is negative. Tobin's Q decreases as the family ownership ratio increases. Firm performance reaches its lowest point when family ownership exceeds 42.53%; then, as family ownership increases, Tobin's Q increases as well. Similarly, as family ownership increases, ROA decreases, and firm performance reaches its lowest point at 65.89%; then, as family ownership increases, firm performance improves.
Keywords: 330; Family ownership; firm performance; ROA(EBITDA); ROA(NI); Tobin's Q; Vietnam